2020
DOI: 10.1007/s13311-020-00922-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiology-Based Treatment of Myoclonus

Abstract: Myoclonus can cause significant disability for patients. Myoclonus has a strikingly diverse array of underlying etiologies, clinical presentations, and pathophysiological mechanisms. Treatment of myoclonus is vital to improving the quality of life of patients with these disorders. The optimal treatment strategy for myoclonus is best determined based upon careful evaluation and consideration of the underlying etiology and neurophysiological classification. Electrophysiological testing including EEG (electroence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(68 citation statements)
references
References 107 publications
1
61
0
Order By: Relevance
“…For both cortical and subcortical myoclonus, which is suspected in the 39 CKCS in this study, if no inciting cause has been identified, levetiracetam has been proposed as a first‐line treatment in humans 2‐4,6,7 . Levetiracetam is unique compared to other AEDs, binding the synaptic protein SV2A 4,23‐25 instead of having a direct effect on GABA receptors.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…For both cortical and subcortical myoclonus, which is suspected in the 39 CKCS in this study, if no inciting cause has been identified, levetiracetam has been proposed as a first‐line treatment in humans 2‐4,6,7 . Levetiracetam is unique compared to other AEDs, binding the synaptic protein SV2A 4,23‐25 instead of having a direct effect on GABA receptors.…”
Section: Discussionmentioning
confidence: 87%
“…Cortical myoclonus might be responsive to medication decreasing cortical excitability, such as standard antiepileptic drugs (AEDs), [2][3][4] although phenobarbital has been shown to be rarely effective in humans. 3 Out of 9 dogs in this study that showed generalized seizure activity, 5 received a first-line antiepileptic medication (imepitoin or phenobarbitone), the remainder did not receive any.…”
Section: Management Of Myoclonusmentioning
confidence: 99%
See 2 more Smart Citations
“…Pena and Caviness then review a physiology-based treatment of myoclonus, a symptom that is often resistant to treatment. Myoclonus is currently best managed by identifying the underlying etiology and using medications that best address the neurophysiological subtype [23]. Tourette syndrome is a heterogeneous neurobehavioral disorder, which develops in childhood, presenting with motor and phonic tics but frequently accompanied by behavioral comorbidities that require a tailored management approach.…”
Section: Therapeutics In Other Movement Disordersmentioning
confidence: 99%